Peran Komik Digital Sebagai Media Visual Dalam Pembelajaran Menulis Narasi Pada Siswa Sekolah Dasar - Erwin Eka Saputra; Chairan Zibar L. Parisu (Jurnal Sultra Elementary School, 2024)
This study aims to explore the role of digital comics as a visual medium in improving elementary school students' narrative writing skills. Through a qualitative-descriptive approach, this study examines the benefits, challenges, and effectiveness of using digital comics in learning. The findings show that digital comics make a positive contribution in helping students understand narrative structures, increasing learning motivation, and encouraging creativity. However, its implementation requires adequate technological support and training for teachers.